Insecticidal Terpenes From the Essential Oils of Artemisia nakaii and Their Inhibitory Effects on Acetylcholinesterase - Liu, Jiayi; Hua, Juan; Qu, Bo; Guo, Xuanyue; Wang, Yangyang; Shao, Meini; Luo, Shihong (Frontiers in Plant Science, 2021)
Essential oils are often the source of insecticidal substances of high efficiency and low toxicity. From GC-MS, column chromatography, and NMR spectra analyses, twenty terpenes were identified from the EOs of Artemisia nakaii. These comprised mostly monoterpenes (49.01%) and sesquiterpenes (50.76%). The terpenes at the highest concentrations in the EOs of A. nakaii were feropodin (200.46 ± 1.42 μg/mL), (+)-camphor (154.93 ± 9.72 μg/mL), β-selinene (57.73 ± 2.48 μg/mL), and 1,8-cineole (17.99 ± 1.06 μg/mL), calculated using area normalization and external standards. The EOs were tested for biological activity, and showed strong fumigant toxicity and significant antifeedant activity against the larvae of Spodoptera litura. Furthermore, the monoterpenes 1,8-cineole and (+)-camphor displayed significant fumigant activity against S. litura, with LC50 values of 7.00 ± 0.85 and 18.16 ± 2.31 μL/L, respectively. Antifeedant activity of the sesquiterpenes feropodin and β-selinene was obvious, with EC50 values of 12.23 ± 2.60 and 10.46 ± 0.27 μg/cm2, respectively. The EOs and β-selinene were also found to inhibit acetylcholinesterase (AchE), with IC50 values of 37.75 ± 3.59 and 6.88 ± 0.48 μg/mL, respectively. These results suggest that monoterpenes and sesquiterpenes from the EOs of A. nakaii could potentially be applied as a botanical pesticides in the control of S. litura.